Artemia as a Strategic Live Feed in Fish and Shrimp Hatcheries: Nutritional Value, Enrichment Technologies, and Implications for Larval Growth and Survival: A Literature Review - Sheny Permatasari (Research and Social Study Institute, 2026)
Background: Live feed availability is a critical factor determining the success of fish and shrimp hatchery operations. Among various live feeds, Artemia remains one of the most widely used organisms due to its suitable particle size, high digestibility, ease of storage, and capacity for nutritional enrichment.Aims: This review aimed to synthesize current knowledge regarding the nutritional value of Artemia, its application in hatchery systems, enrichment strategies, and its effects on larval growth and survival in commercially important aquaculture species.Methods: A systematic literature review was conducted following a structured search of peer-reviewed articles published between 2015 and 2025. Relevant literature was retrieved from Google Scholar, ScienceDirect, SpringerLink, and other scientific databases using predefined keywords related to Artemia, enrichment technologies, hatchery management, and larval performance. Studies were screened based on relevance to fish and shrimp larviculture, nutritional enhancement, and biological performance indicators.Results: The reviewed studies consistently demonstrated that Artemia significantly improves larval growth, specific growth rate, size uniformity, and survival in various aquaculture species, including Litopenaeus vannamei, Penaeus monodon, Oreochromis niloticus, Lates calcarifer, and Clarias gariepinus. Furthermore, enrichment with highly unsaturated fatty acids (HUFAs), omega-3 fatty acids, microalgae, probiotics, synbiotics, vitamins, and phytogenic compounds substantially enhanced the nutritional quality of Artemia, resulting in improved growth performance, immune competence, stress tolerance, and disease resistance.Conclusions: Artemia remains an indispensable live feed in modern hatchery systems. Advances in enrichment technologies have transformed Artemia from a conventional live feed into an effective nutrient delivery platform capable of enhancing larval performance and hatchery productivity. Future development should focus on strengthening domestic Artemia production, improving enrichment efficiency, and integrating biosecure hatchery management practices to support sustainable aquaculture development.